Under the Microscope: Media and Mobile Phone Use among Children and Young People in Portugal - Sara Pereira; Joana Fillol; Daniel Brandão; Mariana Menezes-Neumann (Revista Mediterránea de Comunicación)
Media consumption is heavily influenced by mobile phones and the Internet, especially among younger audiences. Although many studies have demonstrated this, it is essential to continually examine how children's and young people’s relationships with media evolve and affect their lives amid rapid changes in the media ecosystem. Based on an online questionnaire conducted in 26 schools with 1,131 students aged 11 to 19 across Portugal, this study aims to closely examine media usage, particularly mobile phones. By analyzing variables such as school year (corresponding with age) and gender, the research explores mobile phone usage in relation to other media and examines how participants classify themselves as mobile phone users. Findings reveal that children and youth are highly engaged with media, with the mobile phone as the most important device in their lives. The Internet and social networks also rank among the top three most significant media. Time spent on mobile phones increases with school year, correlating with age, and girls use their mobile phones more than boys. More respondents identify as "intensive" or "dependent" users than "moderate" ones. Interestingly, 6th graders (the youngest group) are the most likely to describe themselves as "dependent users." The level of dependency on mobile phones is highlighted by the fact that more than half of the sample would choose their mobile phone as the one object to bring on a long journey.